ACTIVE INTERFERENCE OF STUDENTS OF TOURISM DEPARTMENT, STATE POLYTECHNIC OF BALI IN JAPANESE LANGUAGE LEARNING - Harisal, Harisal Harisal; Kanah, Kanah Kanah (HUMANIKA, 2020)
In studying Japanese, interference is so highlighted because language interference is the most conspicuous source of error among Japanese language learners in the Department of Tourism of the State Polytechnic of Bali. This study aims to describe the type of active interference that arises in students of the Department of Tourism, State Polytechnic of Bali who study Japanese and mentions the factors of active interference. The method used is a qualitative approach to the type of research is descriptive research. The data collected in this study is not in the form of numbers but comes from percentages, field notes, personal documents, notes, memos, and other official documents so that the purpose of this qualitative research is to describe the empirical reality behind the phenomenon in-depth, detailed, and complete. Called descriptive because this study seeks to describe the type of active interference that arises in students of the tourism department, State Polytechnic of Bali. The population in this study were all students majoring in Tourism who came from three study programs who were studying Japanese. While the sample in this study was second-semester students of Hospitality study class D totaling 33 people and class E totaling 34 people, and second-semester students of programs Study of Tourism Business Management class B amounted to 34 people who were taken intentionally (purposive) from 12 classes in three study programs in Tourism department. Based on research, students of the Tourism Department, State Polytechnic of Bali showed a tendency to make an active interference in the lexical field, such as active interference of nouns, verbs, and adjectives. They namely deliberately and consciously incorporating elements of mother language and Indonesian when learning Japanese because of limited dictions, Use of Japanese vocabulary without knowing the function, and the mother tongue / Indonesian language which has taken root.